SOEHARTO’S NEW ORDER, PRESS AND SOCIETY IN TENSION: A Social Reflection - Herdi Sahrasad (Universitas Islam Negeri Alauddin Makassar, 2017)
This article explains that in the Soeharto’s New Order, when the press criticises strongly the state elites, it was easy to accuse the press of being aguinst the law. The word of state elite, the Father, of the Bapak, is law. So, in Indonesian history, since independence, has proved that press closures fluctuate in rhythm with the political situation. From 1951 up to 1965, there were 156 closures of national press. It is only in the period of 1955 and 1956 no closure of press publication. While in the other years, there are closures for instance in 1957, 32 closures, in 1958, 24 closures and the peak of the closures was in 1959 with 38 closures, in 1960, 34 closures and in 1965 there were five closures and a trend which continue in the further years. The press closures reflect the strength of governrnent vis-a-vis society. Sociologically, the government itself is dominated by the Javanese rulers. Their political culture has dominated the national. landscape. Despite the fact that politics, the economy and technology has been changing in the New Order, the strength of Javanese culture has remained. There is no fundamental change in Javanese culture under the Soeharto’s New Order.